Evaluating global progress towards Sustainable Development Goal 7 over space and time by a more comprehensive energy sustainability index - Qi Zhao; Xi Lu; Rachael Marie Fleming (Energy Strategy Reviews, 2025)
Quantifying progress towards achieving the 7th Sustainable Development Goal (SDG7) is essential for tracking global efforts on sustainable energy transition as well as guiding policy development. However, there is a lack of comprehensive assessment frameworks with consideration of temporal-and-regional dynamics. Targeting this research gap, we developed an Energy Sustainability Index (ESI) with 5 dimensions and 12 indicators to measure the progress of SDG7 in 140 countries around the world from 2011 to 2020, with a particular emphasis on its geographical inequality. Results show that while the global average ESI score has increased by 6.7 % from 2011 to 2020, this growth was largely dependent on the rapid development of a few emerging economies, with the growth rate in the rest of the world still lagging. In addition, most of the regions have failed to balance development across the 5 dimensions of the ESI, causing a regression in some dimensions, notably energy reliability. Analysis of inter-population inequality shows that although global inequality in energy development declined by 14.3 % in the period of 2011–2020, the extreme low scores of the Least-Developed Countries (LDCs) remained virtually unchanged, implying that energy development in LDCs needs more attention. This study provides a new paradigm for further exploration in the spatial and temporal characteristics of energy sustainability and highlights the urgency of promoting SDG7 globally in a holistic and synergistic approach.